2019
DOI: 10.1038/s41598-019-38547-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HIV-ART on the restoration of Th17 and Treg cells in blood and female genital mucosa

Abstract: The aim of this study was to evaluate the effectiveness of antiretroviral treatment (ART) on the proportion and functions of Th17 and Treg cells in peripheral blood and female genital tract (FGT) respectively. To this aim, samples from 41 HIV-neg, 33 HIV+ ART-naïve and 32 HIV+ ART+ subjects were obtained. In peripheral blood, altered Th17 and Th17/Treg proportions were normalized in HIV+ ART+, but certain abnormal Treg and activated T-cell proportions were still observed. In FGT, abnormal patterns of secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 62 publications
3
21
1
Order By: Relevance
“…Altered Th17/Treg balance in favour of Tregs is a main cause of gut mucosal immune dysfunction, which facilitates microbial translocation from gut to peripheral blood, promoting generalized inflammation [ 47 , [101] , [102] , [103] ]. In line with previous reports [ 28 , 104 , 105 ], we found a decrease in both Th17 cell frequencies and Th17/Treg ratio during HIV infection, while timing of ART initiation but not duration of ART restored Th17/Treg ratio. We also found a lower Th17/Treg ratio in EC versus other HIV-infected individuals or uninfected controls, contrasting with previous reports [ 74 , 102 , 106 ].…”
Section: Discussionsupporting
confidence: 93%
“…Altered Th17/Treg balance in favour of Tregs is a main cause of gut mucosal immune dysfunction, which facilitates microbial translocation from gut to peripheral blood, promoting generalized inflammation [ 47 , [101] , [102] , [103] ]. In line with previous reports [ 28 , 104 , 105 ], we found a decrease in both Th17 cell frequencies and Th17/Treg ratio during HIV infection, while timing of ART initiation but not duration of ART restored Th17/Treg ratio. We also found a lower Th17/Treg ratio in EC versus other HIV-infected individuals or uninfected controls, contrasting with previous reports [ 74 , 102 , 106 ].…”
Section: Discussionsupporting
confidence: 93%
“…The fact that treated HIV co-infection is associated with reduced IL-17 producing Tcells in the lung is consistent with observations of selective depletion of Th17 from other mucosal compartments, including the gut (76,77) and female genital tract (78).…”
Section: Discussion and Concluding Remarkssupporting
confidence: 88%
“…Failure of ART to restore IL-17 producing T-cells in the female genital tract and the gut mucosa, despite successful reconstitution in the blood, has been linked to reduced CCL20 levels for recruiting Th17 via CCR6 (78,79). However, it is important to note that, in one of the above studies, Th17 were found not to be depleted from bronchioalveolar lavage (BAL) fluid of HIV infected participants (77).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…T reg cells modulate the immune response through regulation of T cell proliferation and differentiation whilst Th17 cells are critical to maintaining mucosal immunity via secretion of IL-17 and the balance of these two cell subsets is therefore critical in providing effective immune function (Valverde-Villegas et al, 2015). Both T reg and Th17 cells have been shown to harbor a high proportion of the LR in therapy suppressed patients and as such, may be an important target in HIV-1 cure efforts (Tran et al, 2008;Alvarez et al, 2013;Sun et al, 2015;Christensen-Quick et al, 2016;Caruso et al, 2019).…”
Section: The Hosts Of the Reservoirmentioning
confidence: 99%